Breakfast Consumption and Academic Achievement Among Chinese Adolescents: A Moderated Mediation Model - Gao, Chun Lei; Zhao, Nan; Shu, Ping (Frontiers in Psychology, 2021)
Studies have shown that a healthy lifestyle has an important impact on the academic achievement of adolescents. Breakfast eating behavior is considered a dietary pattern marker and an essential healthy lifestyle component. The prior study explained that students had a low level of achievement motivation in school because they were exposed to some militating factors in their families such as absenteeism, ill health, malnutrition, and hunger. This study examined the mediating role of achievement motivation and moderating role of socio-economic status in the association between breakfast consumption and academic achievement. Chinese students’ data from the PISA was used as samples. The results showed that: (1) Breakfast consumption had a positive predictive effect on academic achievement; (2) Achievement motivation played a partial mediating role in the relationship between breakfast consumption and academic achievement; (3) Socio-economic status had a moderating effect on the mediating effect of achievement motivation, and socio-economic status moderated the latter half of the mediating process. Besides, both of the two effects were stronger for individuals with higher socio-economic status.